The Effect of Physical Activity on Social Isolation in Elderly - Sri Sunarti; Khonsaa Aadilah Hafizhoh Subagyo; Tita Haryanti; Achmad Rudijanto; Retty Ratnawati; Setyawati Soeharto; Maryunani Maryunani (Acta Medica Indonesiana, 2022)
Background: Elderly people who have poor social relationships have a higher risk of death than those who have strong social networks. Loneliness and social isolation are associated with an increased risk of coronary heart disease and stroke. Physical activity can reduce social isolation, diverting feelings of loneliness by socializing with other people and expanding social networks by participating in the community. This study aimed to determine the effect of physical activity on social isolation in the elderly. Methods: A Cross-sectional study was conducted to 181 respondents. The data is collected through interviewing respondents with the International Physical Activity Questionnaire (IPAQ) and social isolation questionnaires. The data was then analyzed descriptively and calculated using Fisher’s exact test. Setting: Ardirejo and Panggungrejo villages, Kepanjen District, Malang Regency. Results: Based on the Fisher’s exact between  physical activity and social isolation results were obtained p-value 0.000 (PR = 23.407; 95% CI = 3,117-175,800). Conclusion: There is a significant relationship between physical activity and social isolation in the elderly in the community.